2020
DOI: 10.1177/2050640620912877
|View full text |Cite
|
Sign up to set email alerts
|

Post‐induction infliximab trough levels and disease activity in the clinical evolution of pediatric ulcerative colitis

Abstract: Background and aims Recent adult evidence suggests that infliximab (IFX) trough levels (TL) in patients with severe ulcerative colitis (UC) may be decreased. The aims of our study were to compare post-induction IFX TL of children with severe versus moderate UC and to evaluate short- and long-term outcomes. Methods In this single-center retrospective study, children with a diagnosis of UC starting IFX with a Pediatric Ulcerative Colitis Activity Index (PUCAI) ≥35 and with available post-induction TL were recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Endoscopic remission was observed with IFX concentrations ≥6.7 µg/mL at week 14 and ≥3.8 µg/mL at week 30 [36]. These differences seem to suggest that the optimal level of IFX to ensure response or remission may be highly individual and dependent on many factors, including disease severity, as demonstrated in a group of children with UC treated at a dose of 5 or 10 mg/kg in induction [37].…”
Section: Discussionmentioning
confidence: 93%
“…Endoscopic remission was observed with IFX concentrations ≥6.7 µg/mL at week 14 and ≥3.8 µg/mL at week 30 [36]. These differences seem to suggest that the optimal level of IFX to ensure response or remission may be highly individual and dependent on many factors, including disease severity, as demonstrated in a group of children with UC treated at a dose of 5 or 10 mg/kg in induction [37].…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, a recent pediatric cohort demonstrated that adequate infliximab exposure during induction, with post‐induction trough levels ≥5 mg/L, was predictive of endoscopic remission at 6 months (17). In high inflammatory burden states, such as acute severe colitis, data show children in higher trough level quartiles have increased rates of clinical and biochemical remission ( P = 0.01) (35). While, the median pre‐fourth infliximab trough level in pediatric perianal fistulizing clinical responders is significantly higher than in non‐responders (12.7 vs 5.4 µg/mL, P = 0.02) (36).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, however, this study did not report if these changes were statistically significant ( 47 ). A more recent retrospective study confirmed that higher post-induction IFX trough level quartiles were associated with clinical, biological, and combined remission ( 48 ). Another important PK property, immunogenicity, might be predicted by genetic variants.…”
Section: Predicting and Monitoring Response To Medical Therapymentioning
confidence: 92%